An analysis of energy saving through delamping method - Mohd Firdaus Mohd Ab Halim; Muhamad Faizal Yaakub; Mohamad Haniff Harun; Khalil Azha Mohd Annuar; Farriz Hj Md Basar; Mohd Nazri Omar (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Electrical energy consumption is one of the focus areas in Green and Sustainable technology in the 21st century. Many energy consultants offers services to reduce the electricity consumption to the commercial consumer. Many proposals are focusing on selling their energy management system product which cost a lot of initial investment. The problem of applying energy management system is that the building needs major renovation. In this paper, electricity consumption is reduced through delamping method. The delamping is strategizing based on energy efficiency audit. This technique complies with the ASHRAE international standard for office building. The number of light reduced and electricity consumption from this exercise can translate into reduction of maintenance and electricity bill. The comparison of payback period for various energy saving techniques were discussed as well.